Henning Hecht og Torben A.Vestergaard (red.): Portrætter af dansk fiskeri. Dansk Fiskeriforening 1887-1987. Fiskeriforening, 1987). 166 s., 150,-kr. - Ronit, Karsten (Historie/Jyske Samlinger, 1989)
-